PERBANDINGAN KADAR HIGH DENSITY LIPOPROTEIN DARAH PADA PEROKOK AKTIF, PEROKOK PASIF, DAN NONPEROKOK - Fadillah Pasya, Ryan; Irma, Fani Ade (Buletin Farmatera, 2026)
Abstract: Tobacco is one of the factors known to increase the risk of disease and premature death globally. Nicotine is one of the harmful substances in cigarettes that can result in the release of hormones such as catecholamines, cortisol, and growth hormone. The release of these hormones can alter the lipid profile in the blood, including increased total cholesterol levels, Very Low-Density Lipoprotein (VLDL), Low Density Lipoprotein (LDL), and decreased High Density Lipoprotein (HDL) levels. This study aims to determine the comparison of HDL levels in active smokers, passive smokers, and non-smokers.  The total sample in this study was 45 people who were divided equally into three different groups, namely active smokers, passive smokers, and non-smokers. Data analysis was processed using SPSS. Research shows there is a difference in HDL levels between active smokers, passive smokers, and nonsmokers (p0.05). Smoking can significantly lower HDL levels in the blood.